Mitigation of Flow Maldistribution in Minichannel and Minigap Heat Exchangers by Introducing Threshold in Manifolds - P. Dąbrowski (Journal of Applied Fluid Mechanics, 2020)
In the present paper, a detailed numerical investigation has been carried out to analyze the flow maldistribution in 50 parallel rectangular cross-section (1 mm depth and 1 mm width) minichannels and minigap section (1 mm depth and 99 mm width) with rectangular/trapezoidal manifolds in Z-type flow configuration. The author carried out numerical investigation with various mass flow rates, namely 0.05 kg/s, 0.1 kg/s and 0.2 kg/s which results in Reynolds number of 1532, 3064, 6128 respectively. A novel approach for the mitigation of non-uniform flow has been proposed introducing threshold at the entrance of the minigeometry section. The conventional case without threshold (as reference) and 1 mm, 3 mm and 7 mm threshold were introduced. The threshold has been employed by making a manifolds’ depth bigger than section’s depth. The maldistribution coefficient can be reduced twice in minigap section or three times in the minichannel section already with the 1 mm threshold as compared to the arrangement without threshold. It is found that rectangular manifold gives lower maldistribution coefficient than trapezoidal manifold which corresponds with actual state of the art. The distribution is more uniform in minichannel section than in minigap section for the same inlet parameters. To obtain uniform distribution of fluid flow should be stabilized already at the inlet manifold, at the entrance to the minichannel or minigap section. That was done by introducing the threshold in the manifolds, which is novelty of this study.